On Media, On Technology, On Life - Interviews with Innovators - Clay, Arthur; Senior, Timothy J. (Taylor & Francis, 2021)
The book 'On Media, On Technology, On Life: Interviews with Innovators' features thirteen artist-researchers whose artworks reconfigure the relationships between living bodies, microorganisms, tools, techniques, and institutions to ask new questions of life itself. When encountered for the first time, these are works that seem to challenge a conventional understanding of what artists and scientists do. Through the words of the artists themselves, these interviews explore what it means to spearhead innovative new partnerships able to create work that takes on a life of its own. By posing new questions at the interface between media, technology, and life, the book explores themes such as the life of multi-species bodies, the future of food security in the age of biotechnology, the microbial lives of historic archives, and the biohacker communities of the future. Together, they reveal how we are all actors in this theatre of life innovation.